2018
DOI: 10.1111/cch.12546
|View full text |Cite
|
Sign up to set email alerts
|

Working and caring for a child with chronic illness: A review of current literature

Abstract: This review summarizes what is currently known about work patterns, challenges, and consequences in parents of children with chronic conditions. Employment is clearly impacted for these parents. Although workplace challenges have been extensively researched, other challenges (eg, personal and family) and impacts on their well-being have not. This review discusses the present standing of this research. It outlines the strengths and limitations of the current literature, makes recommendations for future research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 64 publications
2
48
0
2
Order By: Relevance
“…We found that patients and families experience substantial burdens of care and challenges in balancing demands of work, school, and other life activities with CTT, though they recognize the importance and benefits of CTT. This is similar to the perspective of parents of children with other chronic illnesses, who report challenges of balancing work and family, time constraints, and stress associated with their child's care [19] and have decreased odds of employment [19,20]. It is possible that the significant burden of care contributes to difficulties with adherence to CTT, which is sub-optimal even among children enrolled in clinical trials of SCD.…”
Section: Discussionsupporting
confidence: 52%
“…We found that patients and families experience substantial burdens of care and challenges in balancing demands of work, school, and other life activities with CTT, though they recognize the importance and benefits of CTT. This is similar to the perspective of parents of children with other chronic illnesses, who report challenges of balancing work and family, time constraints, and stress associated with their child's care [19] and have decreased odds of employment [19,20]. It is possible that the significant burden of care contributes to difficulties with adherence to CTT, which is sub-optimal even among children enrolled in clinical trials of SCD.…”
Section: Discussionsupporting
confidence: 52%
“…This mirrors the literature on family-centered care where there is little consensus between parents and professionals about what family-centered care is, and how it is practice (Coyne, 2015;Kish, Newcombe, & Haslam, 2018;Kou et al, 2012). Furthermore, the inequality in the parent-professional relationship has been offered as a reason for parents' low expectations of family-centered care (Arabiat et al, 2018).…”
Section: Discussionmentioning
confidence: 57%
“…In the context of working with children with long-term conditions and their families, collaboration is particularly salient as these children are primarily cared for at home, with parents taking responsibility for care decisions and delivering treatments (Smith, Cheater, & Bekker, 2015a;Kish, Newcombe, & Haslam, 2018). Furthermore, health professionals advocate working collaboratively with parents when deciding the best cause of action when planning and managing the child's condition .…”
Section: Practice Implicationsmentioning
confidence: 99%
“…The disease follows the person for a long time, compromising their physical, emotional or mental condition. Often, it prevents children from attending school regularly and/or performing their routine childhood activities (2) . Constant visits to the physician, use of medications and the need for hospitalizations may be common, bringing changes in family routine, as they affect children's development and social relationships (3) .…”
Section: Introductionmentioning
confidence: 99%